2013
DOI: 10.1002/rcs.1492
|View full text |Cite
|
Sign up to set email alerts
|

Robotic hepatobiliary and pancreatic surgery: lessons learned and predictors for conversion

Abstract: Robotic-assisted hepatobiliary and pancreatic procedures are often extremely complex, with a significant learning curve. Recognizing factors that prohibit successful completion of a robotic-assisted surgical procedure is key for patient safety. Careful patient selection in the appropriate settings facilitates the maximal benefit of robotic-assisted complex HPB surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 38 publications
1
31
0
1
Order By: Relevance
“…Characteristics of the study included in our review are summarized in Table 2 [9,11,[17][18][19][20][21][22][23]. Nine studies were included in the analysis, including 6 retrospective and 3 prospective.…”
Section: Robotic Distal Pancreatectomy (Rdp)mentioning
confidence: 99%
“…Characteristics of the study included in our review are summarized in Table 2 [9,11,[17][18][19][20][21][22][23]. Nine studies were included in the analysis, including 6 retrospective and 3 prospective.…”
Section: Robotic Distal Pancreatectomy (Rdp)mentioning
confidence: 99%
“…(42) Hence, based on the current evidence, we can only conclude that RDP is feasible and can be performed safely. (7,11,17) However, there is also growing evidence suggesting that RDP may be associated with a shorter learning curve, (15) a lower conversion rate (15) and an increased rate of splenic preservation (11,23,34,38,42) as compared to conventional laparoscopy. In a recent study by Kang et al from Yonsei University, Korea, the authors reported that the rate of splenic preservation was demonstrated a distended bowel with no transition point.…”
Section: Casementioning
confidence: 99%
“…(5,6) However, the adoption of laparoscopic surgery in the fields of liver and pancreatic surgery has been relatively slow. (7,8) Although the first laparoscopic liver and pancreatic resections were reported in the early 1990s, (9,10) widespread adoption of such operations has been hindered by the technical complexities of these procedures, and concerns about oncological margins and risk of bleeding. (8) Pancreatic surgery is among the most complex and challenging of all abdominal operations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…К концу 2015 г. в мировой литературе было опубликовано 426 слу-чаев выполнения этой операции [13][14][15][16][17][18]. Показаниями к операции послужили нейроэндокринная опухоль (29%), протоковая аденокарцинома (23,9%), серозная или муци-нозная цистаденома (22,6%), внутрипротоковая папилляр-но-муцинозная опухоль (20%), другие заболевания (4,5%) [19][20][21][22]. Средняя продолжительность операции соста-вила 278±82,7 мин, интраоперационная кровопотеря -200±131,9 мл [14,23,24].…”
Section: Discussionunclassified